The new materials for battery electrode prototypes - Siburian, Rikson; Hutagalung, Fajar; Silitonga, Oktavian; Paiman, Suriati; Simatupang, Lisnawaty; Simanjuntak, Crystina; Aritonang, Sri Pratiwi; Alias, Yatimah; Jing, Lin; Goei, Ronn; Tok, Alfred Iing Yoong (Multidisciplinary Digital Publishing Institute, 2023)
In this article, we present the performance of Copper (Cu)/Graphene Nano Sheets (GNS) and C—π (Graphite, GNS, and Nitrogen-doped Graphene Nano Sheets (N—GNS)) as a new battery electrode prototype. The objectives of this research are to develop a number of prototypes of the battery electrode, namely Cu/GNS//Electrolyte//C—π, and to evaluate their respective performances. The GNS, N—GNS, and primary battery electrode prototypes (Cu/GNS/Electrolyte/C—π) were synthesized by using a modified Hummers method; the N-doped sheet was obtained by doping nitrogen at room temperature and the impregnation or the composite techniques, respectively. Commercial primary battery electrodes were also used as a reference in this research. The Graphite, GNS, N—GNS, commercial primary batteries electrode, and battery electrode prototypes were analyzed using an XRD, SEM-EDX, and electrical multimeter, respectively. The research data show that the Cu particles are well deposited on the GNS and N—GNS (XRD and SEM—EDX data). The presence of the Cu metal and electrolytes (NH4Cl and MnO2 ) materials can increase the electrical conductivities (335.6 S cm−1 ) and power density versus the energy density (4640.47 W kg−1 and 2557.55 Wh kg−1 ) of the Cu/GNS//Electrolyte//N—GNS compared to the commercial battery (electrical conductivity (902.2 S cm−1 ) and power density versus the energy density (76 W kg−1 and 43.95 W kg−1 ). Based on all of the research data, it may be concluded that Cu/GNS//Electrolyte//N—GNS can be used as a new battery electrode prototype with better performances and electrical activities.